Menumbuhkan Literasi Teknologi Melalui Pengenalan Aplikasi Computer Vision Di Kalangan Pelajar - Muhammad Naufal; Harun Al Azies (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
The purpose of this community service project is to provide education to enhance technological literacy by introducing the basics of Computer Vision applications among students. The activities included a seminar attended by 170 students. An analysis using the Wilcoxon statistical test on pre-post test results showed a significant improvement in participants' understanding of Computer Vision applications. The test results indicated a significant difference before and after the activity with a value of 0.011. Through this community service, participants have successfully grasped the material presented to enhance literacy as change agents in the digital era, positively impacting societal progress through improved understanding of technology in the field of Computer Vision.